IDENTIFIKASI DAN ESTIMASI WILAYAH INTERTIDAL MENGGUNAKAN CITRA ALOS PALSAR, DATA PASANG SURUT DAN DATA DEM (Studi Kasus : Distrik Merauke, Kabupaten Merauke) - , EDWARD WIJAYA; , Abdul Basith, ST. M.Si. Ph.D., ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Intertidal zones are areas that lie between the highest and lowest tide of coastal region. Forms of intertidal zones are affected by two factors: the condition of tidal and coastal topography shape itself. Based on data from Merauke Bappeda note, the slope of the coastal area of Merauke ranges between 0-8 %, categorized as ramps. Tidal ranges at Merauke is also large enough, ranging from 4 to 5 meters. The project was taking District of Merauke in Merauke Regency as a case study. The project used ALOS PALSAR imagery for idetifying coastline of Merauke District, SRTM data for determining coastal slope of Merauke district and TPXO 7.1 models run using TMD (Tidal Model Driver) software for performing tidal predictions. The results of this project are identificated and estimated of intertidal zones and shoreline of Merauke District in the form of maps and area of Merauke District. The results of the analysis show that Merauke district has an instantaneous coastline by 18.172,004 m. The results also show that the shoreline at high tide is 22.934,903 m length, shoreline at low tide is 30.242,489 m length and the identified intertidal area is 4.587.826,299 m2.